Ultra-Long GnRH Agonist Protocol During IVF/ICSI Improves Pregnancy Outcomes in Women With Adenomyosis: A Retrospective Cohort Study - Lan, Jie; Wu, Yaoqiu; Wu, Zexuan; Wu, Yingchen; Yang, Rong; Liu, Ying; Lin, Haiyan; Jiao, Xuedan; Zhang, Qingxue (Frontiers in Endocrinology, 2021)
Objective This study aimed to compare the ultra-long gonadotropin-releasing hormone agonist (GnRH-a) protocol and the long GnRH-a protocol during in vitro fertilization (IVF) or intracytoplasmic sperm (ICSI) treatment on fertility outcomes in women with adenomyosis. Materials and Methods This study was a retrospective cohort study. From January 2011 to May 2018, a total of 371 fresh IVF/ICSI cycles were included. Among the cycles included, 237 cycles of 212 women underwent the ultra-long GnRH-a protocol, while 134 cycles of 116 women underwent the long GnRH-a protocol. The rates of implantation, clinical pregnancy per embryo transfer, live birth, and early miscarriage were estimated between the compared protocols. Results In the study, the early miscarriage rate in women undergoing the ultra-long GnRH-a protocol was significantly lower than those undergoing the long GnRH-a protocol (12.0% versus 26.5%, p = 0.045), whereas the differences in the rates of biochemical pregnancy, implantation, clinical pregnancy, and live birth in women between the two groups showed no statistical significance. The pregnancy outcomes were also sub-analyzed according to the adenomyotic region (diffuse and focal). As for diffuse adenomyosis, the rates of clinical pregnancy and live birth in women undergoing the ultra-long GnRH-a protocol were significantly higher than those undergoing the long GnRH-a protocol (55.3% versus 37.9%, p = 0.025; 43.4% versus 25.9%, p = 0.019, respectively). However, pregnancy outcomes showed no difference between the two protocols in women with focal adenomyosis. Conclusions The ultra-long GnRH-a protocol during IVF/ICSI improves pregnancy outcomes in women with adenomyosis, especially in women with diffuse adenomyosis when compared with the long GnRH-a protocol.